ANALISIS PERHITUNGAN BIAYA KUALITAS (COST OF QUALITY) UNTUK MENINGKATKAN KUALITAS PRODUK - Indra Hermawan; Novitasari Eviyanti (Politeknik Negeri Semarang, 2023)
Abstract : The purpose of this study was to analyze the components of quality costs and calculate the quality costs that occur in ED aluminum with the aim of improving product quality by reducing product defects. This research was conducted by identifying and calculating the cost of quality using the Prevention, Appraisal, and Failure (PAF) method. The research approach used is qualitative research with a case study approach. The object of this research is ED Aluminum, which is the largest aluminum craftsman in Yogyakarta and smelts aluminum into finished goods. The results of this study indicate that ED Aluminum already has activities that are used to improve the quality of the products they produce. Costs incurred to improve quality are employee and partner counseling costs, printing equipment manufacturing costs, machine maintenance costs, raw material inspection costs, work-in-progress inspection costs, finished product testing costs, rework on defective products, and warranty costs. The weakness of the PAF model classification is that it is only able to detect quality costs in financial reports and cannot describe costs that are difficult to identify (hidden costs). Suggestions for further research include explaining hidden costs.